EVALUASI PELAKSANAAN PROSEDUR PENGECEKAN PERSEDIAAN BARANG MASUK PADA PT. TECTRON MANUFACTURING - Ian Sentia; Winanda Wahana Warga Dalam (Jurnal Bisnis Mahasiswa, 2022)
This study report discusses the Evaluation of the Implementation of Inventory Checking Procedures In PT. Tectron Manufacturing. This study report focuses on discussing the inventory checking procedures carried out by IQC (incoming quality control). The background of this writing is that rejected items are often found in the production line, this happens because of the lack of awareness of employees to check according to the established procedures and the lack of accuracy in the checking process due to inadequate IQC checking areas so that when performing visual checks it becomes looks unclear due to dim lighting. The purpose of this study is to improve employee performance in preventing irregularities when checking incoming goods inventory. The research method used by the author is descriptive method and the data collection method is carried out by means of observation, interviews and document inspection. The results of this study indicate that the level of employee compliance at PT. Tectron Manufacturing on the procedure for checking incoming goods inventory has not been effective or it can be said that employees at PT. Tectron Manufacturing has not fully carried out its duties based on the procedures that have been established in the company.